PENINGKATAN HASIL BELAJAR SISWA MELALUI PENERAPAN ALAT PERAGA CIRCULATORY BOTTLE - Meryn Maria Ulva; Siti Nurul Hidayati (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This study proposed to describe the implementation of learning process, students’ responses, and learning outcomes especially in knowledge aspect using the circulatory bottle. This study used a pre-experimental with one group pretest posttest design. Samples consist of 17 students of VIII A class in SMP NU Bahrul Ulum Gresik in the Academic Year 2021/2022. The data were collected using observations, questionnaires, and tests with the instrument such as test assessment sheets, student response questionnaires, attitude, and learning implementation observation sheets. The results showed that: (a) the implementation of learning with circulatory bottle for each stage in three meetings got very good category; (b) the implementation of circulatory bottle got positive responses from students with very good category; (c) learning outcome of social attitude aspects which include cooperative, curiosity, responsibility were declared complete with good and very good predicates; (d) learning outcome in the knowledge aspect increased as evidenced by the average value of N-gain in high category. Based on these results, it can be concluded that the implementation of the circulatory bottle can increase learning outcomes.